2009
DOI: 10.1016/j.ajog.2009.08.015
|View full text |Cite|
|
Sign up to set email alerts
|

Multicenter randomized trial of cerclage for preterm birth prevention in high-risk women with shortened midtrimester cervical length

Abstract: Objective To assess cerclage to prevent recurrent preterm birth in women with short cervix. Study Design Women with prior spontaneous preterm birth <34 weeks were screened for short cervix, and randomly assigned to cerclage if cervical length was <25 mm. Results Of 1014 women screened, 302 were randomized; 42% of women not assigned and 32% of those assigned to cerclage delivered <35 weeks (p=0.09). In planned analyses, birth <24 weeks (p=0.03) and perinatal mortality (p=0.046) were less frequent in the cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
190
0
10

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(202 citation statements)
references
References 24 publications
2
190
0
10
Order By: Relevance
“…In a large multicenter randomized study, Owen et al [6] demonstrated benefits of mid-trimester cerclage placement for patients with singleton pregnancies and a shortened cervix of less than 25 mm. In this study, women with a prior preterm birth and shortened cervix were less likely to have previable births.…”
Section: Discussionmentioning
confidence: 99%
“…In a large multicenter randomized study, Owen et al [6] demonstrated benefits of mid-trimester cerclage placement for patients with singleton pregnancies and a shortened cervix of less than 25 mm. In this study, women with a prior preterm birth and shortened cervix were less likely to have previable births.…”
Section: Discussionmentioning
confidence: 99%
“…Vaginal progesterone has been shown to reduce the rate of preterm birth in women with a short cervix with or without a history of previous preterm birth (34, 4850). Progesterone is as effective as cervical cerclage in women with a prior history of preterm birth and a short cervix (51, 52). Accordingly, additional parameters to cervical length are needed to improve the identification of women at risk of preterm delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Controversies arise in the placement of a cerclage in the presence of a short cervix (<2.5 cm) but not shorter than 1.5 cm, a clinical setting where most experts consider that cervical cerclage can be offered 32 33. Several studies compare expectant versus placement of a physical examination-indicated cerclage showing that, in a very specific population (ie, those with cervical dilation in the absence of labour, bleeding, preterm premature ruptura of membranes or any signs of chorioamnionitis clinically or by amniocentesis), cerclage prolongs gestation and improves neonatal outcomes compared with expectant management 34–36.…”
Section: Discussionmentioning
confidence: 99%
“…Although emergency cerclage with fetal membranes prolapsed into the vagina is actually a salvage operation, there is increasing evidence that it also prolongs gestation and improves neonatal survival compared with expectant management 36–39. In general emergency, cervical cerclage for cervical incompetence is a very difficult procedure with fatal complications like iatrogenic preterm rupture of membranes and chorioamnionitis 14 33 37. Advanced dilation (>3 to 4 cm) and early gestational age (22–24 weeks) are associated with poorer outcomes 36.…”
Section: Discussionmentioning
confidence: 99%